2020
DOI: 10.1002/jcph.1767
|View full text |Cite
|
Sign up to set email alerts
|

Application of PBPK Modeling and Simulation for Regulatory Decision Making and Its Impact on US Prescribing Information: An Update on the 2018‐2019 Submissions to the US FDA's Office of Clinical Pharmacology

Abstract: Since 2016, results from physiologically based pharmacokinetic (PBPK) analyses have been routinely found in the clinical pharmacology section of regulatory applications submitted to the US Food and Drug Administration (FDA). In 2018, the Food and Drug Administration's Office of Clinical Pharmacology published a commentary summarizing the application of PBPK modeling in the submissions it received between 2008 and 2017 and its impact on prescribing information. In this commentary, we provide an update on the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
140
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 8 publications
1
140
0
Order By: Relevance
“…Although limited, there are a number of cases that have successfully used PBPK models to predict transporter‐mediated drug interactions 43 . The PBPK model presented in this article was considered adequate for prediction of DDIs of ivosidenib with CYP3A4, CYP2B6, CYP2C8, CYP2C9, OATP1B1/OATP1B3, and OAT3 substrates by the US Food and Drug Administration (FDA) 26,44 . The capability of the model to predict DDI owing to ivosidenib as a P‐gp inhibitor was considered inadequate by the agency due to lack of mechanism‐based oral absorption model 26,44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although limited, there are a number of cases that have successfully used PBPK models to predict transporter‐mediated drug interactions 43 . The PBPK model presented in this article was considered adequate for prediction of DDIs of ivosidenib with CYP3A4, CYP2B6, CYP2C8, CYP2C9, OATP1B1/OATP1B3, and OAT3 substrates by the US Food and Drug Administration (FDA) 26,44 . The capability of the model to predict DDI owing to ivosidenib as a P‐gp inhibitor was considered inadequate by the agency due to lack of mechanism‐based oral absorption model 26,44 .…”
Section: Discussionmentioning
confidence: 99%
“…The PBPK model presented in this article was considered adequate for prediction of DDIs of ivosidenib with CYP3A4, CYP2B6, CYP2C8, CYP2C9, OATP1B1/OATP1B3, and OAT3 substrates by the US Food and Drug Administration (FDA) 26,44 . The capability of the model to predict DDI owing to ivosidenib as a P‐gp inhibitor was considered inadequate by the agency due to lack of mechanism‐based oral absorption model 26,44 . Although modeling results showed that the inhibition of OAT3 and P‐gp by ivosidenib will have minimal clinical relevance at 500 mg dose level, based on the agency’s feedback, the language for these two transporters was derived for ivosidenib label.…”
Section: Discussionmentioning
confidence: 99%
“…The major PBPK applications (among PBPK-related publications) were associated with the study design, predicting formulation effects and metabolic DDIs, while studying the fate of drugs in special populations, predicting kinetics in early drug development, and investigating transporter-mediated DDIs have increased proportionally over the last decade [ 75 ]. In recent surveys of the PBPK-based submissions to FDA [ 76 , 77 ], about 56–67% of the submissions used PBPK modeling to evaluate the drug interaction potential.…”
Section: Dynamic Pbpk Model For Pk Ddismentioning
confidence: 99%
“…Physiologically based pharmacokinetic (PBPK) models have been increasingly used during drug discovery and development 1,2 for a variety of purposes such as predicting optimal dosing, drug-drug interactions (DDIs), food effects, and pharmacokinetic profiles in specific populations (eg, pediatric subjects, patients with hepatic, or renal impairment). 3,4 As a result, the number of regulatory submissions including PBPK applications submitted to the US Food and Drug Administration (FDA) has significantly increased over the past few years. 5 PBPK models can be developed based on parameters estimated from in vitro tests.…”
mentioning
confidence: 99%